The Relationship Of Human Resources Development And Employee Empowerment With Employee Performance At Maje Camat Office, Kaur Regency - Usi Aradela; Sulisti Afriani; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to find out the relationship between human resource development and employee empowerment and employee performance at the Office of the District Head of Maje District of Kaur. The sample in this study were 28 employees consisting of 17 Civil Servants and 11 honorary people at the Office of the Maje District Head of Kaur Regency, because all populations in this study were sampled, so the method of sampling was by census. The method of data collection used is a questionnaire and the analytical method used is rank spearman correlation and hypothesis testing. Human Resource Development has a strong relationship with employee performance at the Office of the District Head of Maje District of Kaur with a correlation value of 0.760. This illustrates that the more precise the Human Resource Development of employees will increase the level of performance of employees at the Office of the District Head of Maje District of Kaur. Employee Empowerment has a very strong relationship with employee performance at the Office of the District Head of Maje District of Kaur with a correlation value of 0.842. This illustrates that Employee Empowerment at employees of the District Office of Maje District Head of Kaur can support in improving Performance.